2021
DOI: 10.1002/jcla.23990
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intervention strategy of thalassemia for couples of childbearing ages in Centre of Southern China

Abstract: Hemoglobinopathies are the most common Mendelian disorders including abnormal hemoglobin variants and thalassemia in the world. 1 α thalassemia major leads to hydrops fetalis or perinatal death. β thalassemia major and some types of abnormal hemoglobin variants such as hemoglobin S, C compound with β thalassemia minor causes severe anemia. Carrier screening and high-risk couple subjected to prenatal diagnosis are the main content of the thalassemia control plan. 2,3 Population-screening programs for hemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
2
13
0
Order By: Relevance
“…Among the 13,550 patients, 8% were carriers of α-thalassemia, including 4 cases of--SEA /αα (0.37%). These results are consistent with those reported by Jiang et al (Jiang et al, 2021), who did not find any patients with --SEA /αα. ROC curves showed that MCV and MCH (cut-off points of 74.6 fL and 24.4 pg) could effectively identify α 0 -thalassemia carriers and HbH disease.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Among the 13,550 patients, 8% were carriers of α-thalassemia, including 4 cases of--SEA /αα (0.37%). These results are consistent with those reported by Jiang et al (Jiang et al, 2021), who did not find any patients with --SEA /αα. ROC curves showed that MCV and MCH (cut-off points of 74.6 fL and 24.4 pg) could effectively identify α 0 -thalassemia carriers and HbH disease.…”
Section: Discussionsupporting
confidence: 94%
“…In Guangxi, the carrier rate of thalassemia genes is approximately 20%, which is significantly higher than that in other provinces and regions, such as Guangdong (11.6%), Hong Kong (8.4%), Taiwan (5.5%), Sichuan (4.1%), and Jiangxi (2.7%) (Liu et al, 2019;Jiang et al, 2021). As a result, fetal hydrops syndrome (severe α-thalassemia) has consistently been a prominent birth defect in the Guangxi region for many years.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The hemoglobin components were analyzed with a capillary electrophoresis system (Sebia Electrophoresis System, France). According to thalassemia screening guideline 10 and cut‐off value of privious study, 11 a positive result for thalassemia screening was defined as detection of MCV < 82 fL, or MCH < 27 pg, or Hb A 2 > 3.5%, or Hb A 2 < 2.5%, or abnormal hemoglobin zone. When one member of a couple was positive for thalassemia screening, thalassemia genetic testing was performed on both of them.…”
Section: Methodsmentioning
confidence: 99%